Cervical metastasis of gingival carcinoma misdiagnosed as branchiogenic carcinoma, a rare entity - report of a case and review of literature - Qingjia Sun; Mingxing Chen; Yuxin Sun; Xi Chen; Hongjun Xu; Lingjun Rong; Qiong Wu; Dongdong Zhu (BMC, 2017)
Abstract Background A cervical cystic mass is associated with a number of pathologies that present with similar symptoms. These conditions are difficult to differentiate using fine-needle aspiration (FNA), ultrasound (US), computed tomography (CT) and magnetic resonance imaging (MRI). Another dilemma in the differential diagnosis of cervical cystic masses is due to the controversies associated with the existence of branchiogenic carcinoma (BC). BC is an extremely rare disease that must be differentiated from other conditions presenting with cervical cystic masses, especially cystic metastasis from occult primary lesions. Case presentation We present a case report of a right cervical cystic metastasis from a significantly small squamous cell carcinoma primary gingival lesion misdiagnosed as BC by histopathology. A 62-year-old female presented with a painless progressively enlarging cervical mass at the anterior edge of the sternocleidomastoid muscle in the right submandibular region. Preoperative MRI and US revealed a well-defined cystic round mass. Postoperative histological examination indicated BC. Positron emission tomography/computed tomography (PET/CT) revealed high 18F-FDG (18F 2-fluoro-2-deoxy-D-glucose) uptake in surgical regions with a SUV (standard uptake value) max 4.0 and ipsilateral nasopharynx with a SUVmax 4.4, without any distant metastasis. Pathologic results revealed nasopharyngeal lymphadenosis. Considering the low incidence of BC and the limitation of diagnosis in one institution, the patient was referred to another hospital. Physical examination detected a significantly small neoplasm (~3 mm diameter) in the right lower gingiva. Histopathological examination of the neoplasm revealed a well-differentiated squamous cell carcinoma. Surgery, including a partial mandibulectomy and modified neck dissection (neck level I-V and submental lymph nodes) were undertaken. Postoperative histopathological results revealed a well-differentiated squamous cell carcinoma of right lower gingiva and two metastatic lymph nodes in the 18 lymph nodes of level II. A month later, recurrence occurred in the right cervical level II. The patient was placed on postoperative concurrent chemo-radiotherapy and supportive care. The patient suffered from cachexia and survived for only six months after surgery. Conclusions In cases of cervical cystic masses that appear after the age of 40, clinicians should bear in mind that occult primary lesions should be excluded and examination of the gingiva should be undertaken. PET/CT has a limited role in identifying small occult primary lesions and a comprehensive physical examination must be carefully performed.